Investigations of Strain Rate Effects on the Mechanical Properties of Hybrid Composite Laminate Under Varying Temperatures - Erbayrak, Engin; Gumus, Beril Eker; Yuncuoglu, Ercument Ugur; Kahraman, Yusuf (SPRINGER HEIDELBERG, 2020)
The mechanical behavior of hybrid composite laminates under varying strain rates and temperatures was investigated in this study. The hybrid composite laminate is constituted as a sequential stacking sequence of plain-woven carbon-fiber-reinforced epoxy (CFRE) and plain-woven glass-fiber-reinforced epoxy (GFRE) laminates. Vacuum-assisted resin transfer molding (VARTM) process was used to fabricate the composite laminates. Hybrid composite laminates (HCGFRE) were tested under four different strain rates (0.05 min(-1), 0.5 min(-1), 2.5 min(-1), 5 min(-1)) and three different temperatures (RT, 60 degrees C, 100 degrees C). Microstructure analysis was performed to observe the voids, fiber delamination and matrix failure occurring in the composite laminate. In numerical analyses, continuum damage mechanics material model (MAT 58) was utilized in LS-DYNA(R)explicit finite element program to simulate the mechanical properties of CFRE, GFRE and HCGFRE laminates. It was determined that the tensile strength of all composite laminates is increasing by increasing the strain rates in all temperatures. The continuous damage mechanics material model (MAT 58) was found to be suitable for simulating woven composite laminate under different strain rates and temperatures. In microstructural study, it was not observed significant changes in the microstructure of composite laminates by changing strain rates.
Keywords: Hybrid composite; Strain rates; Varying temperatures; VARTM; Continuum damage mechanics material model; FIBER-REINFORCED COMPOSITE; POLYMER COMPOSITES; BEHAVIOR; TENSILE; DAMAGE; CARBON; STRENGTH; MODEL; Science & Technology - Other Topics